Clinical picture of dermatitis herpetiformis - Rybak-d’Obyrn, Joanna; Placek, Waldemar J. (Dermatology Review/Przegląd Dermatologiczny, 2019)
Dermatitis herpetiformis is a rare, chronic, autoimmune blistering disease with hypersensitivity to gluten with the presence of intense pruritus. Symptoms of the disease are symmetrical, polymorphic skin lesions in a typical location. It is thought that dermatitis herpetiformis is a specific skin manifestation of celiac disease, with frequent asymptomatic gluten enteropathy. Both diseases are characterized by the same tissue compatibility antigens, the presence of circulating IgA antibodies against endomysium and transglutaminases, and clinical remission on a gluten-free diet. Non-adherence to this diet predisposes to the development of some tumours, autoimmune and thyroid gland diseases. The diagnosis of dermatitis herpetiformis is based on the findings of the characteristic IgA deposits in the skin papilla in the direct immunofluorescence test. Specific serum antibodies are used as an aid in the diagnosis and for monitoring the compliance with gluten free diet.